2016
DOI: 10.1073/pnas.1610258113
|View full text |Cite
|
Sign up to set email alerts
|

Targeted vaccination against the bevacizumab binding site on VEGF using 3D-structured peptides elicits efficient antitumor activity

Abstract: Therapeutic targeting of the VEGF signaling axis by the VEGFneutralizing monoclonal antibody bevacizumab has clearly demonstrated clinical benefit in cancer patients. To improve this strategy using a polyclonal approach, we developed a vaccine targeting VEGF using 3D-structured peptides that mimic the bevacizumab binding site. An in-depth study on peptide optimization showed that the antigen's 3D structure is essential to achieve neutralizing antibody responses. Peptide 1 adopts a clear secondary, native-like … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…Despite this, the polyclonal antibody response elicited after immunization blocks the receptor binding domain on natural VEGF as well as the binding site for antigen and RFASE as adjuvant [16]. This VEGF therapeutic vaccine has shown antiangiogenic and antitumor activity in pre-clinical models [15], but discrete results in terms of immunogenicity have been observed in the first cancer patients treated with the vaccine [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite this, the polyclonal antibody response elicited after immunization blocks the receptor binding domain on natural VEGF as well as the binding site for antigen and RFASE as adjuvant [16]. This VEGF therapeutic vaccine has shown antiangiogenic and antitumor activity in pre-clinical models [15], but discrete results in terms of immunogenicity have been observed in the first cancer patients treated with the vaccine [17].…”
Section: Discussionmentioning
confidence: 99%
“…This antigen sequence represents the complete Bevacizumab binding site and using RFASE as adjuvant, the vaccine (hVEGF 26-104 /RFASE) induces an immune response with VEGF neutralizing activity and anti-tumor effect [15]. Elicited polyclonal antibody response in addition to its cross-reactivity with human VEGF, have also demonstrated in rats and monkeys its capacity to impair the binding of Bevacizumab to VEGF [15,16], indicating the presence of antibodies that block binding sites on VEGF which have shown to be clinically relevant. This vaccine is being investigated in a phase I open-label clinical trial (NCT02237638), and preliminary results of the first included patients indicated that hVEGF 26-104 /RFASE has a good safety profile.…”
Section: Introductionmentioning
confidence: 99%
“…Using RFASE as adjuvant, the vaccine (hVEGF 26-104 /RFASE) induces an immune response with VEGF neutralizing activity and anti-tumor effect [20]. In rats and monkeys immunized with this vaccine candidate, the VEGFspecific polyclonal antibody response has also demonstrated its capacity to impair the binding of bevacizumab to VEGF, suggesting the presence of antibodies that target the same VEGF epitope as bevacizumab [20,21]. This vaccine is being investigated in a phase I open-label clinical trial (NCT02237638), and preliminary results of the first included patients indicated that hVEGF 26-104 / RFASE has a good safety profile.…”
Section: Introductionmentioning
confidence: 99%
“…This antigen sequence represents the complete bevacizumab binding site. Using RFASE as adjuvant, the vaccine (hVEGF 26-104 /RFASE) induces an immune response with VEGF neutralizing activity and anti-tumor effect [20]. In rats and monkeys immunized with this vaccine candidate, the VEGF-specific polyclonal antibody response has also demonstrated its capacity to impair the binding of bevacizumab to VEGF, suggesting the presence of antibodies that target the same VEGF epitope as bevacizumab [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Using RFASE as adjuvant, the vaccine (hVEGF 26-104 /RFASE) induces an immune response with VEGF neutralizing activity and anti-tumor effect [20]. In rats and monkeys immunized with this vaccine candidate, the VEGF-specific polyclonal antibody response has also demonstrated its capacity to impair the binding of bevacizumab to VEGF, suggesting the presence of antibodies that target the same VEGF epitope as bevacizumab [20,21]. This vaccine is being investigated in a phase I openlabel clinical trial (NCT02237638), and preliminary results of the first included patients indicated that hVEGF 26-104 /RFASE has a good safety profile.…”
Section: Introductionmentioning
confidence: 99%